Slow-paced exercise and time-reversing science have become powerful heart protectors - Tai Chi has opened up a new path for the primary prevention system of cardiovascular diseases with Chinese characteristics - Feng, Xue (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details